MAŁY BIES FIODORA SOŁOGUBA NA SCENACH POLSKICH - Gracla, Jadwiga (Acta Neophilologica, 2015)
The present article focuses on the post-war stage productions of Fyodor Sologub’s The Petty Demon (also known as The Little Demon). The history of stage productions of Sologub’s novel in Poland is discussed. The author notes the absence of a key figure – niedotykomka (little demon) – and the implementation of the stage text of the novel instead of a text of play. Due to these facts, as well as because of the lack of allocation of space into the fantastic and the realistic, the performance does not reflect the ideas of the original text. According to the author, there was a shift in emphasis in the stage performances, damaging the symbolic and decadent nature of the text.